2020
DOI: 10.3390/atmos11111262
|View full text |Cite
|
Sign up to set email alerts
|

Impact of VOCs and NOx on Ozone Formation in Moscow

Abstract: Volatile organic compounds (VOCs), ozone (O3), nitrogen oxides (NOx), carbon monoxide (CO), meteorological parameters, and total non-methane hydrocarbons (NMHC) were analyzed from simultaneous measurements at the MSU-IAP (Moscow State University—Institute of Atmospheric Physics) observational site in Moscow from 2011–2013. Seasonal and diurnal variability of the compounds was studied. The highest O3 concentration in Moscow was observed in the summer daytime periods in anticyclonic meteorological conditions und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
8
30
0
Order By: Relevance
“…10 shows the dependence of the O 3 mass concentration on NOx for different lockdown periods and SII ranges. In general, for all conditions we obtained non-linear relationship between O3 and NOx similar to that obtained by Zillman (1999) and Berezina et al (2020).…”
Section: Meteorological Conditions During the Covid-19 Pandemicsupporting
confidence: 89%
See 1 more Smart Citation
“…10 shows the dependence of the O 3 mass concentration on NOx for different lockdown periods and SII ranges. In general, for all conditions we obtained non-linear relationship between O3 and NOx similar to that obtained by Zillman (1999) and Berezina et al (2020).…”
Section: Meteorological Conditions During the Covid-19 Pandemicsupporting
confidence: 89%
“…One can see that for all SII ranges, O 3 increased more efficiently with an increase in the proportion of organic compounds at the same content of NOx, which is consistent with data analysis shown by Berezina et al (2020). At the same time, in conditions with relatively high SII (i.e.…”
Section: Meteorological Conditions During the Covid-19 Pandemicsupporting
confidence: 87%
“…In Jeddah, a coastal city in Saudi Arabia, the BTEX determinations showed seasonal variation during a one-year experiment, with higher concentrations during the spring and lower concentrations during the autumn [ 21 ]. The results obtained after a long-term (2011–2013) determination of volatile organic compounds in Moskow, Russia, revealed that BTEX made a lesser contribution to O 3 formation in the city [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1]. VOCs are considered major air pollutants because of their significant contribution to the formation of photochemical smog, tropospheric O 3 and secondary aerosols [2][3][4][5]. VOCs negatively affect human health because of their toxic, malodorous, mutagenic and carcinogenic nature [6].…”
Section: Introductionmentioning
confidence: 99%